Synthesis of silica nanoparticles with controllable surface roughness for therapeutic protein delivery. Issue 43 (28th September 2015) - Niu, Yuting; Yu, Meihua; Zhang, Jun; Yang, Yannan; Xu, Chun; Yeh, Michael; Taran, Elena; Hou, Jeff Jia Cheng; Gray, Peter P.; Yu, Chengzhong
Abstract : Silica nanoparticles with controllable surface roughness have been successfully prepared for therapeutic anti-pAkt antibody delivery. Abstract : There is an increasing demand of efficient nano-carriers for intracellular delivery of therapeutic proteins. This study reports on a novel "neck-enhancing" approach to synthesize stable rough silica nanoparticles (RSNs) with controllable surface roughness. By increasing the shell particle size from 13 to 98 nm while fixing the core size at 211 nm, the interspace size between neighboring shell particles of RSNs is enlarged from 7 to 38 nm. Cytochrome c, IgG fragment and IgG antibody are preferably adsorbed onto one of the RSNs with the interspace size of 14, 21 and 38 nm, respectively. The binding activity of the IgG fragment loaded onto RSNs is maintained as confirmed by surface plasmon resonance. The hydrophobically modified RSN with the interspace size of 38 nm effectively deliver the therapeutic anti-pAkt antibody into breast cancer cells, causing significant cell inhibition by blocking pAkt and the downstream anti-apoptotic protein Bcl-2.